Determinants of Purchase Decisions for Honda Vario Automatic Motorcycles in Bandung City: The Role of Product Design, Product Quality, and Price - Tubagus Muhamad Turnawan; Veronika Santi Paramita (Commercium : Journal of Business and Management, 2026)
The development of the Indonesian two-wheeled automotive industry has intensified competition in the automatic motorcycle segment, highlighting the importance of factors influencing purchasing decisions. The purpose of this study aims to analyze the effects of product design, product quality, and price on purchasing decisions for Honda Vario automatic motorcycles in Bandung City. A survey method was used in a quantitative research approach, and data was gathered by distributing questionnairesto Honda Vario consumers. Respondents were selected probabilitas sampling according to preset standards, yielding a total sample of 100 consumers. Multiple regression analysis was used to examine the relationships between variables. The results indicate that product quality and price have a positive and significant effect on purchasing decisions, while product design does not show a significant effect. These findings suggest that consumers of Honda Vario prioritize functional performance and economic considerations over visual design aspects when making purchasing decisions. The study provides practical implications for manufacturers and marketers to emphasize product quality improvement and competitive pricing strategies.